Assessing Poverty Measurement Practices and Statistical Capacity in Central America - World Bank (Washington, DC, 2012)
It is important for countries to measure and track poverty as frequently and accurately as possible, particularly in Central America. That information allows identifying the poor and keeping them on the agenda, understanding the evolution of poverty trends over the short and long term, assessing the determinants of poverty, targeting policy interventions geared to poor people, and evaluating the effectiveness of policy actions. The need to frequently updating and collecting precise and inclusive poverty data is critical for countries in Central America, a sub-region that has proven vulnerable to various types of shocks in the past (including the recent fuel, food price, and financial crises from 2007-2008). Of particular importance for governments and donors is the issue of calculating poverty at high levels of geographic disaggregation to help them best target policy interventions for poor and vulnerable populations, while efficiently allocating resources. Notwithstanding important advances in recent years, there are a variety of elements in current poverty measurement and mapping practices in Central America that are susceptible to further improvement. The purpose of this note is to take stock of current poverty measurement practices and the status of statistical capacity for effective poverty measurement in Central America. The first section reviews the main aspects that characterize poverty methodologies currently employed by each of the six countries in Central America, laying out similarities and differences and highlighting where there's room for improvement. The second section takes a closer look at national statistical capacity for poverty data collection and evaluation, with a special focus on periodicity. The final section lays out the key constraints to poverty measurement in Central America parsed out by the topics of poverty measurement methodology, poverty mapping, and statistical capacity.